Peningkatan Keterampilan Menulis Cerita Pendek Menggunakan Metode Mind Mapping Siswa SMPN 26 Makassar - Syamsinar; Kembong Daeng (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
This study aims to improve the ability to write short stories using Mind Mapping of class IX students of SMP Negeri 26 Makassar. The research method used was classroom action research conducted in two cycles. The sample of this research was class IX students of SMP Negeri 26 Makassar, totalling 23 students. Research data were obtained through planning, action implementation, observation and reflection through tests, class observation, and documentation. The results showed that in cycle I about 13.04% or 3 out of 23 students who managed to reach the completion criteria and as many as 86.96% or 20 out of 23 students who did not reach completeness. However, after improvement and repetition through the second cycle, the percentage of students who reached the KKM increased significantly to 82.60%. This shows that the use of the Mind Mapping method can improve learning outcomes in writing short stories.